The Effectiveness of Scaffolding Strategy to Increase Students’ Reading Comprehension at Elementary School UPTD SDN 14 Parepare - Darmawati, Darmawati; Mujahidah, Mujahidah; Sunubi, Abdul Haris; Dalle, Ambo; Arqam, Arqam (Universitas Muhammadiyah Barru, 2026)
This study examined the effectiveness of scaffolding strategies in improving reading comprehension among 30 fifth-grade students at UPTD SDN 14 Parepare, utilizing classroom action research based on the Kemmis and McTaggart model across two iterative cycles spanning three months. Data were gathered through pre- and post-cycle reading tests evaluating literal, inferential, and critical comprehension skills, supplemented by structured observations of instructional delivery and student participation. In Cycle 1, the average comprehension score was 67.89, with only 40% of students meeting the minimum mastery criterion of 70, while engagement averaged 79.70%. Following refinements such as enhanced peer collaboration and visual aids, Cycle 2 yielded a mean score of 87.53, achieving 100% mastery and 86.37% active engagement. These findings underscore scaffolding's role in providing graduated support to bridge proficiency gaps, promoting learner autonomy in main idea identification, vocabulary application, and inferential reasoning. Grounded in sociocultural theory, the strategy fosters equitable literacy development in elementary English settings and equips educators with practical tools to enhance teaching efficacy. Ethical considerations were upheld by obtaining informed consent from parents and school authorities while ensuring participant anonymity and voluntary involvement throughout the research process. Future studies may explore digital integrations to expand applicability.